PERILAKU PETANI DALAM PENGGUNAAN PESTISIDA HUBUNGANNYA DENGAN PENURUNAN AKTIFITAS KERJA ENZYM CHOLINESTERASE PADA PETANI TEMBAKAU. (Studi KasusPetani Penyemprot HamaTembakau di DesaMontok, Kecamatan Larangan, Kabupaten Pamekasan) - Manggala Krisna Sugiharto; Ngadino .; Iva Rustanti (Poltekkes Kemenkes Surabaya, 2013)
Organophosphate pesticide is majorly used in the farming industries to protect plants fromdestructive organism. Most farmers generally use pesticide since it is considered as the mostsecure and useful way to protect plants from destructive organisms, however most of them alsodo not realize that the use of pesticide in a long period will affect to the health and bodyresistance, especially it will affect the cholinesterase enzyme activities.The aim of this research was to describe the relationship between cholinesterase enzymeactivities and the behavior of pesticide users, where samples were taken from tobacco farmersin Montok, Pamekasanin 2013.This research was using analytical methods, where statistical data examinations are used in thedata processing. In terms of time arrangements, this research was using crossectional methodswhere dynamic correlation among risks factors and effects are studied.From the results of this research, it was known that cholinesterase enzyme activities ofrespondents have low toxic level (47.2%), (83.3%) farmers have sufficient knowledge ofpesticide used, (80.6%) farmers have sufficient behaviors of pesticide used, (72.2%) farmershave sufficient practices of pesticide used.The research can be concluded that the farmer's knowledge level and practices did notsignificantly correlate with cholinesterase enzyme activities. Meanwhile, farmers actions showedsignificant correlation to cholinesterase enzyme activities with value of p = 0.002 0.05.Therefore, it is necessary for Agriculture Department to hold a routine training for farmers onhow to use pesticide in a proper way and environmentally manner.Keywords: Behaviors, cholinesterase, pesticide, farmers